The Effectiveness of Self-Assessment to Improve Metacognitive Ability in Islamic Religious Education - Septa Miftakul Janah; Tasman Hamami (Ta'dib, 2022)
The weakening of the metacognitive ability of adolescent students, especially at the junior high school level is very important to note. Because metacognition ability has implications for students' ability to solve problems in the end on their learning outcomes. Improved metacognition skills can be done through models, learning strategies, and assessments of learning PAI subjects. Increasing students' metacognitive abilities can be done through a complete self-assessment so that they can assess all aspects of competence to improve students' metacognitive abilities. This study aims to elaborate on how the effectiveness of the self-assessment model in PAI learning in junior high schools can improve students' cognitive abilities. This research was conducted at SMP Negeri 2 Ponorogo using a qualitative approach. Data collection through interviews and documentation. Data analysis was carried out interactively and continuously until it was completed using the Miles & Huberman model, including condensation data, data display, and conclusion drawing. This study revealed that the students of SMPN 2 Ponorogo who conducted an effective self-assessment showed an increase in their metacognitive ability. They succeeded in increasing their metacognition ability by conducting self-regulation through reflection during the self-assessment. In addition, students can understand the PAI material in-depth, marked by a critical attitude to ask questions, provide feedback to the teacher, and solve problems so that PAI learning leads to student-centeredness.